KETAHANAN GENOTIPE KEDELAI TERHADAP KEKERINGAN DAN KEMASAMAN, HASIL INDUKSI MUTASI DENGAN SINAR GAMMA - WIDIATI GIONO, B.RINI; -, MUH. FARID BDR -; NUR, AMIN; SOLLE, MUCHTAR S.; IDRUS, IZDDIN (Jurnal Agroteknos, 2014)
The study aimed to classify soybean genotypes that are tolerant, moderate and sensitive to drought and acidity. The results are expected to give a contribution in the development of Soyban on dry land and acid soil. Increasing of genetic diversity was carried out through mutation induction by gamma ray in soybean seeds. The experiment was conducted in green house by using the method in the form of a two-factor factorial design laid out in the draft group. The first factor was the variety (V) which consisted of three kinds, namely soybean Menyapa varieties (v1), Orba (v2), and Tanggamus (v3). The second factor was the dose of gamma-ray irradiation (D) consisted of 4 doses of 0 Gy (d0), 25 Gy (d1), 50 Gy (d2), and 75 Gy (d3) at concentrations of PEG and Al which showed that the level of diversity the biggest concentration of 30 previous trials of PEG+10 ppm Al. The volume of nutrient solution (Hoagland's) maintained in accordance with the initial volume by adding distilled water, and the solution was maintained at pH 4 using NaOH and HCl 1N. The results showed that the grouping was based on drought tolerant and acidity as follows: genotypes tolerant were varieties Menyapa 50 Gy gamma irradiation, variety of Orba 25 Gy of gamma irradiation, gamma irradiation variety Tanggamus 0 Gy, 25 Gy, 50 Gy of gamma iradiation. Moderate genotype were varieties Menyapa 75 Gy of gamma irradiation, variety Orba 50 Gy, 75 Gy of gamma irradiation, variety Tanggamus 75 Gy of gamma irradiation; genotype susceptible were variety Menyapa 0 Gy, 25 Gy of gamma irradiation; variety Orba without gamma irradiation of 0 Gy.